Educational outcomes and leadership to meet the needs of modern health care. (1st December 2001) - Spencer, J; Jordan, R
Abstract : If professionals are to be equipped better to meet the needs of modern health care systems and the standards of practice required, significant educational change is still required. Educational change requires leadership, and lack of educational leadership may have impeded change in the past. In practical terms standards refer to outcomes, and thus an outcome based approach to clinical education is advocated as the one most likely to provide an appropriate framework for organisational and system change. The provision of explicit statements of learning intent, an educational process enabling acquisition and demonstration of these, and criteria for ensuring their achievement are the key features of such a framework. The derivation of an appropriate outcome set should emphasise what the learners will be able to do following the learning experience, how they will subsequently approach these tasks, and what, as a professional, they will bring to their practice. Once defined, the learning outcomes should determine, in turn, the nature of the learning experience enabling their achievement and the assessment processes to certify that they have been met. Provision of the necessary educational environment requires an understanding of the close interrelationship between learning style, learning theory, and methods whereby active and deep learning may be fostered. If desired change is to prevail, a conducive educational culture which values learning as well as evaluation, review, and enhancement must be engendered. It is the responsibility of all who teach to foster such an environment and culture, for all practitioners involved in health care have a leadership role in education. Quality in Health Care(Quality in Health Care 2001;10(Suppl II):ii38–ii45)